Predictive factors for sustained virological response after treatment with pegylated interferon α-2a and ribavirin in patients infected with HCV genotypes 2 and 3. - Claus Niederau (Public Library of Science (PLoS), 2014)
Background Previous trials have often defined genotype 2 and 3 patients as an "easy to treat" group and guidelines recommend similar management. Aims The present study looks for differences between the two genotypes and analyzes predictive factors for SVR. Methods Prospective, community-based cohort study involving 421 physicians throughout Germany. The analysis includes 2,347 patients with untreated chronic HCV genotype 2 (n = 391) and 3 (n = 1,956) infection treated with PEG-IFN α-2a plus ribavirin between August 2007 and July 2012. Results When compared with genotype 2 patients, those with genotype 3 were younger, had a shorter duration of infection, lower values of total cholesterol, LDL cholesterol and BMI, a higher frequency of drug use as infection mode and male gender (p<0.0001, respectively), and a higher APRI score (p<0.005). SVR was higher in genotype 2 when compared with genotype 3 (64.7% vs. 56.9%, p = 0.004). By multivariate analysis of genotype 2 patients, low baseline γ -GT and RVR predicted SVR. In genotype 3 age ≤45 years, cholesterol>130 mg/dl, a low APRI score, and a γ-GT ≥3-times ULN, RVR, and RBV starting dose were associated with SVR by multivariate analysis. Conclusions The present study corroborates that liver fibrosis is more pronounced in genotype 3 vs. 2. SVR is higher in genotype 2 versus genotype 3 partly because of follow-up problems in genotype 3 patients, in particular in those infected by drug use. Thus, subgroups of genotype 3 patients have adherence problems and need special attention also because they often have significant liver fibrosis. Trial registration Verband Forschender Arzneimittelhersteller e.V., Berlin, Germany ML21645 ClinicalTrials.gov NCT02106156.